2022
DOI: 10.3390/jpm12040537
|View full text |Cite
|
Sign up to set email alerts
|

The Maintained Glycemic Target Goal and Renal Function Are Associated with Cardiovascular and Renal Outcomes in Diabetic Patients Following Stent-Supported Angioplasty for Renovascular Atherosclerotic Disease

Abstract: Patients with type 2 diabetes mellitus (T2DM) constitute a large proportion of patients with atherosclerotic renal artery stenosis (ARAS). However, the mechanism of impaired renal function and hypertension in this subset of patients is multifactorial. We aimed to investigate whether, in diabetic patients, renal function (RF), systolic (SBP) and diastolic blood pressure (DBP) values following stent-supported angioplasty (PTA) for ARAS have an impact on cardiovascular and renal outcomes. Methods: The study group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In the recent elegant study by Badacz R, the authors aimed to investigate whether, in diabetic patients, the renal function (RF) and systolic (SBP) and diastolic blood pressure (DBP) values following stent-supported angioplasty (PTA) for atherosclerotic renal artery stenosis (ARAS) have an impact on cardiovascular and renal outcomes. In a group of 99 adult patients, they proved, among others, that major cardiac and cerebral events (MACCE) and progression to renal replacement therapy (RRT) were higher among those who did not reach the target glycemic goals compared to well-maintained T2DM at 24 months observation [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the recent elegant study by Badacz R, the authors aimed to investigate whether, in diabetic patients, the renal function (RF) and systolic (SBP) and diastolic blood pressure (DBP) values following stent-supported angioplasty (PTA) for atherosclerotic renal artery stenosis (ARAS) have an impact on cardiovascular and renal outcomes. In a group of 99 adult patients, they proved, among others, that major cardiac and cerebral events (MACCE) and progression to renal replacement therapy (RRT) were higher among those who did not reach the target glycemic goals compared to well-maintained T2DM at 24 months observation [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the treatment of choice for RAS is percutaneous transluminal angioplasty (PTA), generally combined with stent implantation, which significantly reduces the incidence of recurrent stenosis and improves long-term outcomes [ 120 , 141 , 146 , 148 , 149 ]. It has a low complication rate of less than 5% in experienced centers and an acceptable stenosis recurrence rate of approximately 15% [ 148 , 149 ].…”
Section: Epidemiology Risk Factors and Clinical Course Of Atheroscler...mentioning
confidence: 99%
“…The above findings have been questioned due to the uneven distribution (few cases with severe stenosis) of patients that excluded patients who could potentially benefit from interventional therapy [11]. Recently, multiple small studies have demonstrated that patients with ARAS who have severe complications, such as resistant hypertension and rapid decline of kidney function, are more likely to benefit from interventional treatment [12][13][14][15]. Therefore, it is a clinical challenge to select patients with potential benefits to assist in the development of clinically optimized treatment options for patients with ARAS (Fig.…”
Section: Introductionmentioning
confidence: 99%